Odor mixtures of opposing valence unveil inter-glomerular crosstalk in the Drosophila antennal lobe - Ahmed A. M. Mohamed (Nature Portfolio, 2019)
Fruit flies need to appropriately respond to mixtures of attractive and repellent odors in their natural environment. Here, the authors propose that lateral inhibition between glomeruli activated by attractants or repulsive odors mediates the appropriate response.